Pesan abadi bumi dan langit kepada manusia: analisis komunikasi dakwah dalam tradisi pembacaan Kitta Tulkiyamat dalam masyarakat Makassar - Mappaselleng, Nur Setiawati; Ahmad Zaharuddin Sani Ahmad Sabri, (Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2016)
Investigations on naskhah Tulkiyamat conducted in the village of Sanrobone, Takalar regency is intended to examine the elements contained in Naskhah Tulkiyamat, as media of preaching on the people of Makassar. The results of the study on naskhah Tulkiyamat show this naskhah contains elements of Islam as faith, morals, Sharia and Sufism. While Text-Messages are delivered as a medium of preaching includes the message of the faith, the sublime character, willingness to sacrifice, honesty, and friendship. This study used a qualitative approach to understand the perceptions and behavior of the people in the tradition of Tulkiyamat reading in Sanrobone. Bys using analysis of communication and preaching approach then some parts chapter and article in Tulkiyamat manuscript will be inventoried and analyzed that related to the teachings of Islam which gave messages of preaching. Especially for this paper, there will analyzed messages of preaching contained in chapter 3 and article 3 which tells the story of "the voice from the sky and earth". Based on the analysis of the article 3, for a description of the meaning and messages preaching that can be taken as learning is about; (1) temptations of life in the world, (2) the need to maintain a manner of speaking, (3) the importance of always repent, (4) the primacy and importance of always reading Al-Qur’an. It is hoped that the tradition of reading Tulkiyamat can be maintained and was always carried out the study of the moral values of Islam contained therein.